IMPLEMENTASI METODE CERAMAH DALAM PELAKSANAAN PEMBELAJARAN KELAS RANGKAP DI SEKOLAH DASAR - balqis, cindi balqis nabila; nabila, cindi balqis; Wapa, Andi; Arrasyid, Harun (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2024)
The aim of this research is to apply the lecture method in multigrade learning at SDN 1 Kaligung, Banyuwangi Regency, East Java Province. This research uses a library study method where data is collected through journals, books and other relevant sources. Multigrade learning using the lecture method in elementary schools can determine learning styles or methods using traditional methods. With the existence of a learning model using the lecture method, it can increase understanding of the material, it can also be seen that the application of the lecture method can provide maximum results, it is truly proven that there is an increase in student learning motivation. With the lecture method learning, it is hoped that learning activities can be carried out effectively and efficiently, and it can be concluded that with this, teachers can make efforts to use lecture methods that are creative and more interesting for pupils and students. The application of multigrade learning methods using the lecture method increases learning motivation and improves students' learning understanding.